Persepsi Konsumen dari Personal Brand Korean Celebrity Endorser terhadap Brand Love dengan Mediasi Lokal Brand Equity - Evelyn, Brigitta; Christina, Nathania; Yosevina, Christiana; Amelia, Novi (Universitas Prasetiya Mulya, 2024)
The phenomenon of the Korean wave in Indonesia has changed and influenced the perception of Indonesian society. In view of this phenomenon, various Indonesian local brands in the skincare industry use Korean Celebrity as a celebrity endorser in their marketing strategy that will have an effect on local brand equity to ultimately affect brand love. The theories applied to the study are celebrity endorsers, local brand equity, and brand love. The study also used a quantitative approach through the dissemination of a questionnaire with a total of 288 respondents and statistical tests to find a supposed relationship with SEM methods using AMOS 24 software. The findings of this study produced information in the world of marketing in the local brand industry Indonesia, that is there was a significant positive relationship between expertise and local brand equity, but the results of this research showed no influence between attractiveness and local brand equity.